معايير الإفصاح بالقوائم المالية الخاصة بالمصارف التجارية بين التحكم المؤسسي ورقابة المصرف المركزي - العربيد, عصام فهد (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تكتسب معايير الإفصاح في القوائم المالية الخاصة بالمصارف التجارية أهمية خاصة نظرا" لحساسية قطاع المصارف ,حيث يحرص المصرف المركزي على سلامة الوضع المالي للمصارف حتى إذا كان على حساب الإفصاح الكافي، وينصب التحكم المؤسسي على المساهمين ولجان التدقيق وآليات مجالس الإدارة وتوفير أسس اختيار المدراء التنفيذيين الذين يخدمون مصالح المساهمين. لقد شهدت الاقتصاديات في كل من الولايات المتحدة الأمريكية واليابان وألمانيا انهيار العديد من المصارف التجارية الضخمة نتيجة المبالغة في تضخيم الأرباح وسوء الإفصاح المالي في القوائم المالية لهذه المصارف التجارية، وذلك بسبب سوء التحكم المؤسسي وعدم الالتزام بالسلوك المهني والأخلاقيات المهنية وضعف الرقابة التي يفرضها المصرف المركزي في مثل هذه الحالات. إن تحقيق الموازنة بين متطلبات الإفصاح ورقابة المصرف المركزي والتحكم المؤسسي يمثل موضوع هذا البحث بحيث نضمن الإفصاح الكافي وتوفير متطلبات التحكم المؤسسي ومتطلبات الرقابة للمصرف المركزي وقد قدم هذا البحث عدة نماذج لمعالجة المشكلة من اليابان وألمانيا والولايات المتحدة الأمريكية، وخلص البحث إلى عدة نتائج وتوصيات يمكن الأخذ بها كنموذج مناسب للإفصاح والتحكم المؤسسي ورقابة المصرف المركزي The disclosure Standards of the financial lists, which are specific to commercial banks, gain special importance due to the sensitivity of banking where the central bank makes sure of the safety of the financial status even if it is on the account of sufficient disclosure and the way it controls the contributors, the checking committees and the mechanism of the board and provides the bases of selecting the executive directors that serve the interests of the contributors. The economics of the United States, Japan, and Germany have witnessed the collapse of several large commercial banks due to the exaggeration in the profits and the wrong financial disclosure of the financial lists of these banks because of the weak control on the side of the government and the existence of no commitment to the career morals and behaviors besides the lack of proper surveillance imposed by the central bank in such cases. The achievement of the balance between the disclosure needs and the central bank surveillances and the government control is the aim of this research where we guarantee the proper disclosure as well as the needs of government control and the central bank surveillance. This research introduces many patterns to solve this problem taken from Japan, Germany and the United States and reaches many conclusions and recommendations that can be taken as proper basis of application.